Using Access Control List against Denial of service attacks (مجلة العلوم الاقتصادية والسياسية, 2017)
The network security is very important in our daily life as people using the internet everywhere such as e-commerce, e-government, e-learning…..etc. One of the major threat on the network is denial of service attacks DoS. This paper studied DoS attacks, by launching them in a networked scenario and then demonstrated their effects. The objective of the study is to use Access control list ACL to stop these attacks. Wireshark had been used to monitor and analyze the flow of the packets. The administrator can decide whether there is DoS attacks or not based on server's resources (CPU usage, memory used) which are very high refer to unusual flood of packets. ACL has been used to stop the unusual flood. Cisco packet tracer had been used to demonstrate the DoS attacks and applied the ACL. This paper showed that the DoS attacks can be applied easily by the attackers and can be stopped easily using ACL by the administrator. The DoS attacks could be launched any way just the administrator has to stop it in early stage. This paper recommended that the administrators has to keep monitoring the network behaviors changes to stop the flooding.